2003
DOI: 10.1021/nl0259380
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activation Energy for Grain Growth in Nanocrystalline Yttria-Stabilized Zirconia

Abstract: Nanocrystalline (∼15−20 nm) 3 mol % yttria-stabilized zirconia (3YSZ) powder is synthesized via sol−gel technique. A reduced activation energy value of ∼13.0 ± 0.9 kJ/mol is observed for grain growth in nano-3YSZ powder, within the calcination temperature range of 400−1200 °C, which is much lower than that (580 kJ/mol) reported for submicron/micron-sized 3YSZ. This is attributed to large oxygen-ion vacancy concentration in nano-3YSZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
83
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 28 publications
9
83
2
1
Order By: Relevance
“…We have found no particular reduction in the activation energy as seen in ceramic nanocrystalline materials. 33 We have also found that in fcc nanocrystalline materials, twins appear in a mechanism that is similar to that postulated for larger grain materials, with an activation energy similar to that of grain-boundary diffusion. The activation energy that we found for grain-boundary migration of 34.7 kJ/ mol compares well with that found in previous studies in other fcc materials and with different interaction potentials which are in the the range of 24-31 kJ/ mol.…”
supporting
confidence: 69%
“…We have found no particular reduction in the activation energy as seen in ceramic nanocrystalline materials. 33 We have also found that in fcc nanocrystalline materials, twins appear in a mechanism that is similar to that postulated for larger grain materials, with an activation energy similar to that of grain-boundary diffusion. The activation energy that we found for grain-boundary migration of 34.7 kJ/ mol compares well with that found in previous studies in other fcc materials and with different interaction potentials which are in the the range of 24-31 kJ/ mol.…”
supporting
confidence: 69%
“…ZrO 2 shows versatile polymorphism with three different crystal structures: cubic (c-ZrO 2 ), tetragonal (t-ZrO 2 ) and monoclinic (m-ZrO 2 ) [17,18]. The point symmetry of the Zr site is C 2h and D 4h for the monoclinic and tetragonal form, respectively, indicating that the local monoclinic structure is less symmetric than tetragonal as well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zhou and Huebner [6] showed a significant enhancement of oxygen-vacancy concentration in nanocrystalline ceria as compared to conventional ceria powder. Shukla et al [7] proposed that this enhancement in oxygen-vacancy concentration may be one of the reasons for the reduced activation energy for the grain growth of nanocrystalline yttria-stabilized zirconia.…”
mentioning
confidence: 99%